(untitled) (Med Phoenix, 2022)
Introduction: Placental thickness (PT) plays vital role when the menstrual age is not known. The present study was undertaken to calculate the Placental thickness at level of insertion of umbilical cord and correlate it with gestational age and fetal weight, subsequently establishing a nomogram for Placental thickness at different age of gestations. Materials and Methods: A total of 300 antenatal women from 12 to 40 weeks of gestation with singleton pregnancy and with no high-risk factor were included in the study from October 2021 to July 2022. Ethical approval was taken from institutional review committee (Ref. F-NMC/541/078-79). A detailed history was taken from all the patients. Basic antenatal investigations, clinical and ultrasonography examination were done. Results: In present study the mean age group of pregnant women was 23.92 ± 4.456 years with mean age of gestation to be 28.18 ± 7.450 weeks. Most common location of placenta is found to be Anterior (32%). There is very strong correlation between placental thickness with gestational age r=0.987 and estimated fetal weight r=0.873. P-value was 0.001 in both. Conclusion: Ultrasonographic measurement of Placental thickness, gestational age and estimated fetal weight play a vital role in antenatal care. Thus, with advancing gestational age; placental thickness measurement can be an additional tool to determine gestational age and fetal weight. Any deviation from normal value can prompt to any developing abnormalities.